Pelatihan Pembuatan Google Form Sebagai Media Pembelajaran Jarak Jauh - Roni Priyanda; Nishbah Fadhelina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
This community service was carried out in October 2020 at SMP Negeri 5 Langsa, as a form of dedication by the service team in answering problems that often arise in distance learning, especially in the city of Langsa, the selection of SMP Negeri 5 Langsa as a forum for service this time is due to its very close location. with a dedicated campus which is also a priority in education development, especially in the city of Langsa. All teachers participated in this community service by sharing fields of study at SMP Negeri 5 Langsa. The steps taken by the first service team are conducting initial studies and field surveys, in order to analyze the problems that occur and then seek solutions so that the problems that occur can be minimized. The second stage was the implementation of the activity, to determine the success in this stage of the activity the servant gave a questionnaire using google form related to participant opinions regarding the benefits, advantages or disadvantages of using google form as a medium for giving online assignments. The third stage analyzes whether the implementation of the service is carried out effectively or not. The final results of the average assessment of the participants showed that 91.74% of participants agreed that the use of Google Forms as an effective online medium and of the 11 indicators given each showed that more than 85% of participants gave positive responses.